The Representation of the Child on Social Media: Interpretive Content Analysis of Parental Trolling TikTok Videos - Zuzanna Sury; Sara Zygmuntowicz; Ewelina Dziubla (Jagiellonian University Press, 2024)
This article examines the phenomenon of parental trolling videos on TikTok, where parents engage in pranks involving their children as part of platform challenges. The study investigates communication methods, user demographics, and algorithmic influences on content dissemination. Findings suggest potential psychosocial implications for children resembling cyberbullying, raising concerns about future parent-child relationships and the risk of social normalization of abuse of children's images on the Internet. Authors advocate for increased pedagogical education for parents, and recommend more social campaigns and research on predictors and effects of parental trolling, highlighting the need for holistic education and therapeutic support for children affected by the misuse of their image. The article shows some probable effects of publicizing images of children by parents, taking into account the impact of individual parents' decisions on entire societies. This topic opens a new, relevant area of pedagogical reflection.